2004
DOI: 10.1016/j.newast.2004.06.004
|View full text |Cite
|
Sign up to set email alerts
|

The iron Kα lines as a tool for magnetic field estimations in non-flat accretion flows

Abstract: Observations of AGNs and microquasars by ASCA, RXTE, Chandra and XMM-Newton indicate the existence of broad X-ray emission lines of ionized heavy elements in their spectra. Such spectral lines were discovered also in X-ray spectra of neutron stars and X-ray afterglows of GRBs. Recently, Zakharov et al. (2003) described a procedure to estimate an upper limit of the magnetic fields in regions from which X-ray photons are emitted. The authors simulated typical profiles of the iron Kα line in the presence of magne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 136 publications
(148 reference statements)
0
8
0
Order By: Relevance
“…However, instead of solving the shadow formation problem by numerical simulations, one can use the approach developed by Zakharov (1994bZakharov ( , 1995; Zakharov & Repin (1999, 2002a,b, 2004a, 2003bZakharov et al (2004);Zakharov (2004);Zakharov & Repin (2005a), Zakharov et al (2005a,b). Mirages are boundaries of bright images, and shadows are also generated for accretion disks.…”
Section: Searches For Mirages Near Sgr a * With Radioastronmentioning
confidence: 99%
“…However, instead of solving the shadow formation problem by numerical simulations, one can use the approach developed by Zakharov (1994bZakharov ( , 1995; Zakharov & Repin (1999, 2002a,b, 2004a, 2003bZakharov et al (2004);Zakharov (2004);Zakharov & Repin (2005a), Zakharov et al (2005a,b). Mirages are boundaries of bright images, and shadows are also generated for accretion disks.…”
Section: Searches For Mirages Near Sgr a * With Radioastronmentioning
confidence: 99%
“…Even if we consider a supermassive black hole in the center of the quasar M SMBH = 10 9 M , then its Schwarzschild radius is r g = 3× 10 14 cm and assuming that the emission region for the X-ray radiation is located near the black hole r emission < 100 r g = 3 × † Simulations of X-ray line profiles are presented in a number of papers, see, for example, Zakharov & Repin (2002a,b,c,d, 2003a, 2003c) and references therein, in particular Zakharov et al (2003) showed that an information about magnetic filed may be extracted from X-ray line shape analysis; Zakharov & Repin (2003b) discussed signatures of X-ray line shapes for highly inclined accretion disks, Zakharov et al (2004a) calculated shapes of spectral lines for non-flat accretion flows. 10 16 cm, we obtain that r emission < R EC , therefore the point size source approximation can be adopted for the X-ray emitting region.…”
Section: Cosmological Distribution Of Microlensesmentioning
confidence: 99%
“…The new Penning-trap experiment at the MPIK in Heidelberg, called ALPHATRAP [34], primarily aims at the g factor of heavy few-electron ions, including boronlike.Since the discovery of the quadratic Zeeman effect [35,36] numerous experimental studies in atoms and molecules have been accomplished [37][38][39][40]. The nonlinear Zeeman effect is important in astrophysics due to the strong magnetic field at the stellar objects [41][42][43]. It is also relevant for atomic clocks, magnetometers and other high-precision experimental setups as a source of the 2 P J fine structure J = 1/2 J = 3/2 Zeeman splitting 1st order M J = −1/2 M J = +1/2 M J = −3/2 M J = −1/2 M J = +1/2…”
mentioning
confidence: 99%